Pemetaan Digital dan Analisis Spasial Vegetasi Bernilai Konservasi di Kecamatan Tanah Sareal, Kota Bogor - Efri Gresinta; Aan Risdiana; Fitri Damayanti; Acep Musliman (Universitas PGRI Silampari, 2026)
Tanah Sareal District is an urban area with a high level of urbanization and land conversion, potentially reducing the presence of conservation-value vegetation. This study aims to identify, analyze, and map the distribution of urban vegetation with conservation value using a Geographic Information System (GIS)-based spatial approach. The research method uses a descriptive quantitative approach through field surveys, Landsat 8 and Sentinel-2 image analysis, Normalized Difference Vegetation Index (NDVI) analysis, and overlay techniques, kernel density, and vegetation fragmentation analysis. The results show that more than two-thirds of the area is dominated by built-up areas, while high-density vegetation (NDVI > 0.5) is only found in limited areas such as river banks, green open spaces, and educational areas. The identified conservation-value vegetation includes Tanjung (Mimusops elengi), Kecapi (Sandoricum koetjape), Beringin (Ficus benjamina), Bisbul (Diospyros blancoi), and Pulai (Alstonia scholaris), with a fragmented distribution pattern. This study shows that GIS-based digital mapping effectively supports vegetation conservation planning and strengthens green open spaces in urban areas.